2001
DOI: 10.1109/16.960374
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-spike epilayer technology applied to bipolar transistors

Abstract: Abstract-For the first time, epilayers with an arsenic-doped spike of 50 nm width have been grown and used in silicon bipolar junction transistors (BJTs). The epilayer has been optimized such that the collector-base junction of the BJT is formed within the arsenic spike. The counterdoping of boron out-diffusion by arsenic strongly reduces the basewidth. The portion of the spike that is not counterdoped increases the total amount of n-type doping in the collector without reducing ceo . The increased collector-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The decrease of the deposition rate with As surface coverage is governed by the same physical principle as the decrease in the growth rate. It was already shown that As deposition stops after forming a full monolayer [9], and this form of the deposition rate was chosen according to the typically observed dependence of the sticking coefficient on coverage [8]. In Fig.…”
Section: Parameter Dependenciesmentioning
confidence: 99%
“…The decrease of the deposition rate with As surface coverage is governed by the same physical principle as the decrease in the growth rate. It was already shown that As deposition stops after forming a full monolayer [9], and this form of the deposition rate was chosen according to the typically observed dependence of the sticking coefficient on coverage [8]. In Fig.…”
Section: Parameter Dependenciesmentioning
confidence: 99%
“…However, using arsine is challenging due to its strong tendency to segregate on the surface and subsequent auto-doping behavior. Past work has shown that these properties can be controlled and applied with benefit to create special doping profiles [ 8 , 9 ]. Here a technique is developed for a controlled segregation, removal and auto-doping of As to obtain the required very lowly-doped profiles.…”
Section: Introductionmentioning
confidence: 99%